(untitled) (Journal of the College of Basic Education, 2022)
Number of elements as Sulpher and Oxygen can be found as sulphides and oxides in steel, and as they have low solubility in steel, they are presented as non-metallic inclusions. The shape, number, size and distribution of these inclusions have a significant influence on the comportment of steel in various engineering applications. The object of this study is to examine the shape and type of non-metallic inclusions by using chemical reagents and to determine the indices K0 which give the percentage amount of these inclusions in the structure of steel. Then to investigate the relation between these indices and mechanical properties. It is concluded that ductility and shock resistance are inversely proportional to the indices, which tensile strength is proportional directly with these indices.